2004
DOI: 10.1111/j.1365-2524.2004.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

A delay they can ill afford: delays in obtaining Attendance Allowance for older, terminally ill cancer patients, and the role of health and social care professionals in reducing them

Abstract: Despite a growing interest in holistic care for the terminally ill, financial needs are often not addressed. This is reflected in the fact that some people with a terminal illness are not accessing disability benefits, despite eligibility. The present paper is based on a study investigating delays experienced by cancer patients in obtaining Attendance Allowance (AA) by special rules, and missed opportunities for professionals to assist with claims. The study took place in a hospice where patients were referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
(4 reference statements)
0
14
0
1
Order By: Relevance
“…Research by the UK-based MacMillan Cancer Support organisation found that terminally ill patients with cancer of working age were repeatedly required to undergo work capacity assessments and work-focused interviews to gain access to income support payments and that the assessment processes were not sensitive to the problems faced by people with cancer 13. Policies such as these result in unnecessary delays for patients and carers seeking support and also lead to underutilisation of programmes that are designed to buffer the economic impact of illness 5. A streamlined process for assessment for government-funded support would improve access to and the use of these programmes; and minimise the burden faced by patients and carers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by the UK-based MacMillan Cancer Support organisation found that terminally ill patients with cancer of working age were repeatedly required to undergo work capacity assessments and work-focused interviews to gain access to income support payments and that the assessment processes were not sensitive to the problems faced by people with cancer 13. Policies such as these result in unnecessary delays for patients and carers seeking support and also lead to underutilisation of programmes that are designed to buffer the economic impact of illness 5. A streamlined process for assessment for government-funded support would improve access to and the use of these programmes; and minimise the burden faced by patients and carers.…”
Section: Discussionmentioning
confidence: 99%
“…While out-of-pocket costs account for only a small proportion of the total cost of care provided to patients receiving end-of-life care, their impact on the household can be severe as costs can escalate rapidly, often depleting a household's economic and social resources at a time when they are already burdened by a loss of income and assets. Furthermore, rapidly changing needs of terminally ill patients and their family carers are not accommodated well in the assessment and eligibility processes of social welfare programmes5 and other support services such as respite care.…”
Section: The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Relating the findings to the limited available literature backs up existing research that individuals in the UK struggle with the benefits system when left to deal with it alone [40]. Furthermore, people affected by cancer in the UK miss out on benefits to which they are entitled in the absence of specialist services [3,4] and that there are considerable additional costs associated with cancer treatment [22]. Uniquely, this study has a longitudinal element, and follow-up interviews are currently underway which will enable a more in-depth examination of the impact of the cancer trajectory on finances.…”
Section: Discussionmentioning
confidence: 87%
“…This may result in difficulties affording the additional resources required to cope with illness [2], as well as adding further strain to the process of dealing with cancer. However, such financial pressures are not often discussed with health professionals [3,4]. Evidence shows that cancer is likely to affect patients' incomes although there appear to be differential effects depending on the type of cancer [5] and whether those affected are still in employment or retired [6].…”
Section: Introductionmentioning
confidence: 99%